Cesarean Section Rate, Maternal and Fetal Outcome of Birth Following Cesarean Section at Finoteselam Hospital, Northwest Ethiopia: A Descriptive Retrospective Data (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: cesarean section rate; maternal and neonate outcomes; northwest ethiopia